Modeling Instruction to Promote Student’s Understanding of System and Model of System of Mechanical Energy - Zainul Mustofa; Anik Asmichatin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Understanding of system and model of the system are necessary for conducting an analysis of scientific phenomena. One concept in science that requires system is energy. This research aimed to understand how modeling instruction promoted increasing student’s understanding system and model of a system on mechanical energy material. Research was conducted on 30 students of MIA at SMAN 1 Kertosono. The result showed that student’s understanding of the system and model of the system increased significantly. Series of learning in class showed that at every meeting session, student skill increased from novice to expert. They were able to show how important the system explain the mechanism of energy transfer were. Average N-gain 0.32 (medium category) indicated that modeling instruction was good enough to promote student understanding of the system. Moreover, any misconception about energy was able to prevent and overcome by this learning. By learning, student’s skill to solve new problem had changed approaching expert problem solver. كان فهم أنظمة ونماذج الأنظمة ضروريًا لإجراء تحليل لظواهر العلوم. واحدة من المفاهيم في العلوم التي تتطلب النظام كانت الطاقة. يهدف هذا البحث إلى فهم كيفية تعزيز إرشادات النمذجة فهم الطلاب لأنظمة ونماذج الأنظمة على مواد الطاقة الميكانيكية. أجريت البحوث على 30 طالب من MIA 1 في SMAN 1 Kertosono. أظهرت النتيجة أن فهم الطلاب لنظام ونموذج النظام زاد بشكل كبير. أظهر تسلسل التعلم في الفصل كل جلسة اجتماع ، زادت مهارة الطلاب من المبتدئ إلى الخبير. يمكنهم شرح آلية نقل الطاقة. يشار إلى متوسط N-gain 0.32 (الفئة المتوسطة) أن النمذجة جيدة بما فيه الكفاية لتعزيز فهم الطلاب للنظام. علاوة على ذلك ، كان أي سوء فهم حول الطاقة قادراً على منع هذا التعلم والتغلب عليه. من خلال التعلم ، مهارة الطالب لحل مشكلة جديدة تقترب من حلول المشاكل.